Diversity and zoogeography of the terrestrial mollusks of the sierra of Tamaulipas, Mexico - Correa-Sandoval, Alfonso; Rodríguez-Castro, Rubén; Venegas-Barrera, Crystian Sadiel; Horta-Vega, Jorge Víctor; Barrientos-Lozano, Ludivina; Rodríguez-Castro, Jorge Homero (Instituto de Ecología, A.C., 2017)
Diversity and biogeography of Mexican terrestrial gastropods is poorly known. The terrestrial mollusks of the Sierra of Tamaulipas were surveyed from October 1988 to November 2005. A total of 482 samples were obtained from 30 localities, characterized with different vegetation types. Thirty-one genera and 46 species belonging to 18 families are recorded. The primary zoogeographical relationships are characterized by the presence of neotropical and neartic affinities (17 species: 37%) and the endemic taxa (11 species: 24%). The family Spiraxidae has the largest number of endemic species (6). The biogeographical value in this area is 3.78.